Religiosity In The Novel Merdeka Sejak Hati By Ahmad Fuadi - Awaliah, Siti Fatimah; Hartati, Dian (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2021)
This research is motivated by the waning of norms of decency and morals. Based on these problems, the purpose of this study is to describe the value of religiosity contained in the novel Merdeka Sejak Hati By Ahmad Fuadi. The research method is descriptive qualitative with content analysis. Data collection technique is literature study with observation. Research stages: searching, reading, listening and taking notes. The results of the analysis show that the value of religiosity includes: faith (tauhid), including faith, piety, and repentance; behavior (morals), including patience, humality, trustworthiness, honesty, sincerity, and discipline; and norms of life (fiqh), including halal, haram, makruh, mubah and sunat.